Carbon nanomaterial with photochromism and water stimulation response as well as preparation method and application of carbon nanomaterial

By preparing and covering carbon dots in polyvinyl alcohol, combining ultraviolet light and water stimulation, photochromicity and reversible changes in water response are achieved, multi-stimulus response problems in the prior art are solved, applied to the fields of information encryption and anti-counterfeiting, and the application potential of carbon dots is expanded.

CN119875274APending Publication Date: 2025-04-25YAOLING TIMES (SHANDONG) NEW ENERGY TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510056072.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing photochromic carbon dot materials have challenges in multi-stimulus response, mainly due to the difficulty in designing their complex structures and interactions between particles.

Method used

By preparing carbon dots containing electron-deficient aromatic imine groups and coating them in polyvinyl alcohol, it is prepared by microwave-assisted synthesis, combining ultraviolet light and water stimulation to achieve reversible photochromic and water-responsive properties.

Benefits of technology

It has realized the photochromic and water stimulation response of carbon nanomaterials, reversible changes, and has been successfully applied to the fields of information encryption and anti-counterfeiting, expanding the application potential of carbon dots in the design and functionalization of multifunctional photoelectric materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875274A_ABST
    Figure CN119875274A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanomaterial with photochromism and water stimulation response as well as a preparation method and application thereof. The preparation method comprises the following steps: A, preparing carbon dots containing electron-deficient aromatic imine groups; and B, uniformly mixing the carbon dots prepared in the step A, a component A and diethylamine in a solvent according to a certain proportion, and drying to obtain the carbon dots, wherein the component A is selected from one or more of polyvinyl alcohol, polypropylene glycol and polyethylene glycol. The photochromic characteristic and the stimulation response behavior of the carbon dots are successfully combined, a feasible path is provided for developing a nanometer material capable of controlling the appearance and the photoactivity characteristic at the same time, a new thought is provided for design and functionalization of the photochromic carbon dots, and the application potential of the carbon dots in the fields of information encryption, anti-counterfeiting and the like is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functional materials, and in particular to a carbon nanomaterial with photochromic and water stimulation response, and a preparation method and application thereof. Background Art

[0002] In recent years, photoresponsive materials have attracted widespread attention in the fields of bioimaging, sensors, anti-counterfeiting and security detection equipment. The light-triggered response can be efficiently adjusted by precisely controlling the irradiation wavelength and intensity, and the emission wavelength and other luminescent properties of the photoresponsive material can be effectively adjusted. Among the photoresponsive phenomena, photochromism and photoluminescence are particularly eye-catching, which are manifested as changes in appearance color and fluorescence color, respectively. Combining organic materials with different photoluminescent properties with materials with photochromic properties is of great significance in the development of high-performance multifunctional photoresponsive materials. Among these photoresponsive luminescent substances, the ability to undergo reversible changes in emission and appearance color under external stimuli has attracted the interest of many scientific researchers due to its scarcity and huge application potential, and research on this part is also particularly urgent.

[0003] Carbon dots (CDs), as an emerging zero-dimensional luminescent carbon nanomaterial, have unique optical and physical properties. During the synthesis process, its optical properties can be effectively adjusted by adjusting the conjugated domain, doping elements and functionalized surface groups. Carbon dots have attracted widespread attention due to their outstanding characteristics such as high fluorescence stability, excellent biocompatibility, and environmentally friendly preparation process. In addition, the fluorescence properties of carbon dots can be combined with photochromism to show dynamically adjustable color changes under external stimuli, thereby exhibiting multifunctional light response characteristics. However, most of the photochromic carbon dot emissions reported so far are mainly limited to the combination of photochromism and fluorescence, and face the challenge of multi-stimulus response. This is mainly due to the difficulty in structural design of multifunctional nanomaterials with complex structures and particle interactions. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon nanomaterial with photochromic and water stimulation response and a preparation method and application thereof to overcome the shortcomings of the prior art in order to solve the above-mentioned problems.

[0005] The technical solution adopted by the present invention is as follows: A method for preparing a carbon nanomaterial having photochromic and water stimulus response, characterized in that it comprises the following steps:

[0006] A. Preparation of carbon dots containing electron-deficient aromatic imine groups;

[0007] B. The carbon dots prepared in step A, component A and diethylamine are uniformly mixed in a solvent in a certain proportion, and then dried to obtain the carbon dots; wherein component A is selected from one or more of polyvinyl alcohol, polypropylene alcohol, and polyethylene glycol (preferably polyvinyl alcohol), and the carbon dots are coated in component A; the carbon nanomaterial has photochromic and water stimulus response characteristics.

[0008] Further, in step A, raw material A, biuret and diethylamine are used as precursors to prepare carbon dots by microwave-assisted synthesis; wherein raw material A is selected from one or more of naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic anhydride and phthalic acid, preferably naphthalenetetracarboxylic acid.

[0009] Furthermore, in step A, naphthalenetetracarboxylic acid and biuret are mixed and ground evenly, and then diethylamine and deionized water are added to prepare carbon dots by microwave-assisted synthesis.

[0010] Further, the mass ratio of naphthalenetetracarboxylic acid to biuret is 2-4:150-250, for example, it can be 2:150, 2:160, 2.5:180, 3:200, 3:210, 3.5:230, 3.8:240, 4:250, etc. The amount of naphthalenetetracarboxylic acid should not be too much or too little. Too much will lead to excessive carbonization of the reaction, reduce the surface functional groups of carbon dots, reduce the yield, and increase the reaction cost. Too little will reduce the contact opportunity of the precursor during the reaction, making it difficult to produce a structure with ultraviolet light response.

[0011] Furthermore, a mixture of naphthalenetetracarboxylic acid, biuret, diethylamine and deionized water was heated by microwave, cooled naturally to room temperature, washed with water for several times, and dried to obtain carbon dots.

[0012] Furthermore, the mass volume ratio of naphthalenetetracarboxylic acid to diethylamine is 20-40:0.5-1.5, expressed in g / L, for example, it can be 20:0.5, 20:0.6, 25:0.7, 30:0.8, 30:1, 35:1.2, 40:1.5, etc.

[0013] Further, in step B, the mass ratio of carbon dots to coating material is 200-400:1, for example, it can be 200:1, 210:1, 220:1, 250:1, 280:1, 300:1, 350:1, 400:1, etc. The amount of coating material should not be too much or too little. Too much will lead to too low carbon dot concentration in the material, increased response time of the composite material, and poor ultraviolet light response effect. Too little will lead to too high carbon dot concentration, uneven mixing of carbon dot solution and coating material, and non-uniform ultraviolet light response time.

[0014] Further, in step B, the mass volume ratio of carbon dots to diethylamine is 20-40:1, in g / L, for example, 20:1, 21:1, 22:1, 25:1, 28:1, 30:1, 35:1, 40:1, etc. The amount of diethylamine should not be too much or too little. Too much will result in too fast response time, making it difficult to observe the actual change process with the naked eye, affecting further practical use. Too little will result in only a small number of sites on the surface of the carbon dots reacting, increasing the response time and weakening the response effect.

[0015] Furthermore, the present invention also includes a carbon nanomaterial having photochromic properties and water stimulation response, and the carbon nanomaterial is prepared by the above-mentioned preparation method.

[0016] Furthermore, the present invention also includes an application of the above-mentioned carbon nanomaterial in the field of information encryption and anti-counterfeiting, that is, utilizing the photochromic and water stimulation response characteristics of the carbon nanomaterial to achieve repeated writing, hiding and erasing of information, and the information can only be read under the stimulation of a specific wavelength of light.

[0017] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0018] 1. The present invention prepares carbon dots containing electron-deficient aromatic imine groups, and coats the carbon dots in polyvinyl alcohol to achieve photochromic and water-responsive reversible properties. The photochromic property is achieved by forming free radical anions induced by ultraviolet light, while the water-responsive reversibility originates from the breaking and regeneration of hydrogen bonds between the carbon dots and polyvinyl alcohol. By adjusting the light intensity and water wetting conditions, the optical properties of the carbon dots can be reversibly changed, and the application of security information anti-counterfeiting and multi-level data encryption has been successfully realized.

[0019] 2. The present invention successfully combines the photochromic properties of carbon dots with stimulus-responsive behavior, providing a feasible path for the development of nanomaterials that can simultaneously control both appearance and photoactive properties. It also demonstrates a feasible method for constructing multifunctional optoelectronic materials with advanced applications. This provides new ideas for the design and functionalization of photochromic carbon dots, and expands the application potential of carbon dots in the fields of information encryption and anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a TEM image of carbon dots (CDs) prepared in Example 1 of the present invention;

[0021] Figure 2 is the XRD pattern of carbon dots (CDs) prepared in Example 1 of the present invention;

[0022] Figure 3 is a Fourier transform infrared spectrum of carbon dots (CDs) prepared in Example 1 of the present invention;

[0023] Figure 4 is an elemental analysis diagram of carbon dots (CDs) prepared in Example 1 of the present invention; wherein, Figure 4 (a) is the XPS spectrum of carbon dots. Figure 4 (b)- Figure 4 (d) are C1s spectrum, N 1s spectrum and O 1s spectrum respectively;

[0024] Figure 5 It is a UV-visible absorption spectrum of a mixed solution of carbon dots (CDs) and diethylamine (30 mg of carbon dots + 1 mL of diethylamine + 1 mL of deionized water) prepared in Example 1 of the present invention before and after UV irradiation;

[0025] Figure 6 This is an EPR test graph of the CDs@PVA film prepared in Example 1 of the present invention before and after UV irradiation;

[0026] Figure 7 This is a graph showing changes in infrared peak values ​​of the CDs@PVA film prepared in Example 1 of the present invention after being soaked and before and after being irradiated with ultraviolet light;

[0027] Figure 8 is a graph showing changes in infrared peak values ​​of the CDs@PVA film prepared in Example 1 of the present invention before and after irradiation with ultraviolet light after immersion and drying;

[0028] Fig. 9 This is the experimental performance of the CDs@PVA film prepared in Example 1 of the present invention in terms of information input and erasure;

[0029] Fig.10 : are photos of the CDs@PVA film prepared in Example 1 of the present invention before and after being irradiated with light after carrying optical information; wherein, Fig.10 (a) and (b) are photos before and after ultraviolet irradiation. Fig.10 (c) is a photograph of the film after it was wetted and dried in sunlight. DETAILED DESCRIPTION

[0030] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0032] Example 1

[0033] A method for preparing a CDs@PVA film comprises the following steps:

[0034] S1. Preparation of carbon dots

[0035] S11, 30 mg of naphthalenetetracarboxylic acid and 2.06 g of biuret were mixed and ground evenly, and then the mixture was transferred to a 25 mL beaker, 1 mL of DETN (diethylamine) and 4 mL of deionized water were added, and mixed to obtain a mixed solution;

[0036] S12, placing the mixed solution in a microwave oven, heating it at the defrosting setting for 15 min, cooling it naturally to room temperature, then washing the solid with water several times, and finally drying the solid in an oven at 60° C. overnight to obtain white solid carbon dots;

[0037] S2. Preparation of PVA solution

[0038] Dissolve 10 g of polyvinyl alcohol 1750±50 (PVA) in 100 mL of deionized water to obtain a solution, put the solution into an oil bath, and heat it at 90° C. and 700 r / min for 10 h to obtain a PVA solution with a mass fraction of 10%;

[0039] S3. Preparation of CDs@PVA film

[0040] Take 1 mL of the PVA solution obtained in step S2, mix it evenly with 30 mg of the carbon dots obtained in step S1 and 2 mL of diethylamine solution to obtain a mixture, add the mixture dropwise onto a glass slide, let it stand and dry naturally for 2 h, and then further dry it in an oven at 60 °C to obtain a CDs@PVA film.

[0041] like Figure 1 As shown, Figure 1 The TEM data of CDs prepared in this example are shown. CDs are monodispersed spherical particles with an average diameter of 3.9±0.3 nm and a lattice spacing of 0.31 nm, which is consistent with the 002 plane spacing characteristics of graphite carbon.

[0042] like Figure 2 As shown, Figure 2 The XRD data of the CDs of this example are shown. The CDs have an obvious diffraction peak at 2θ=26.1°, which corresponds to the (002) crystal plane of graphite carbon. The XRD peak is consistent with the TEM image data of the CDs.

[0043] like Figure 3 As shown, the functional groups of the CDs of this example were analyzed by Fourier transform infrared spectroscopy. Figure 3 Middle, located at 3430cm -1 The absorption peaks at 1645 cm indicate the presence of -OH and -NH2 groups in the carbon dots, which provide favorable reaction sites for further modification of the carbon dots. -1 The absorption peak at 1730 cm corresponds to the stretching vibration of the C=O / C=C bond, while the absorption peak at 1730 cm-1 The nearby peaks correspond to the stretching vibration of C—N bonds. These results indicate that the surface of carbon dots contains rich functional groups.

[0044] In order to explore the structure, surface composition and graphitization degree of the carbon dots prepared in this example, the inventors conducted elemental analysis on the carbon dots. Figure 4 As shown, Figure 4 (a) shows that carbon dots have characteristic peaks at 284.8eV, 400.0eV and 531.0eV, corresponding to carbon, nitrogen and oxygen elements respectively. High-resolution XPS spectroscopy further studied the surface chemical composition of carbon quantum dots. C 1s peak ( Figure 4 (b)) was deconvoluted into three distinct peaks, confirming the formation of a covalent bond between naphthalenetetracarboxylic acid and biuret. The deconvoluted peaks at 283.4 eV, 285.2 eV, and 286.8 eV corresponded to C—C / C=C, C—N, and C=O bonds, respectively. 26 Similarly, the high-resolution O1s spectrum ( Figure 4 (c)) confirmed the existence of C=O bonds, with deconvoluted peaks at 531.2eV and 532.5eV, which were attributed to C=O and C—O functional groups, respectively. In addition, the high-resolution N1s spectrum ( Figure 4 (d) shows peaks at 400.8 eV and 401.9 eV, which are attributed to C—N and —NH2 bonds, respectively. It is worth noting that the XPS results are highly consistent with the FTIR results, providing a comprehensive insight into the surface chemical properties and structural composition of carbon quantum dots.

[0045] In order to study the fluorescence properties of the mixed solution of carbon dots and diethylamine, the inventors recorded the UV-visible absorption spectra of the carbon dot solution ((a solution formed by mixing 30 mg of carbon dots + 1 mL of diethylamine + 1 mL of deionized water)) before and after irradiation. Before irradiation, the UV-visible absorption spectrum of the carbon dot solution showed an absorption peak at 210 nm, indicating the presence of an aromatic C=C structure in the carbon core. After irradiation with 365 nm ultraviolet light, the inventors observed that the absorption peak at 210 nm weakened, and additional absorption peaks appeared in the range of 300-600 nm, such as Figure 5 As shown in Figure 2, this change originates from the photoinduced electron transfer on the surface of carbon quantum dots. The carbon dot solution was mixed with PVA and dried to obtain a CDs@PVA film. The structural changes of the CDs@PVA film before and after UV irradiation were further observed to better understand its response mechanism. By examining the infrared peaks of the CDs@PVA film before and after UV irradiation, the inventors found that the peaks did not change significantly, as shown in Figure 2. Figure 6 As shown in Figure 2, this indicates that the UV response of CDs@PVA film comes from delocalized free radicals, which is confirmed by its EPR test results. For the water-induced response mechanism, the inventors analyzed the changes in the infrared peaks of CDs@PVA film after immersion and drying, as shown in Figure 2. Figure 7As shown in the figure, after the CDs@PVA film is immersed, its wavelength at 3300 cm -1 The hydroxyl peak near the -1 , which is a sign of hydrogen bond breaking. Figure 8 As shown in Figure 2, after immersion and drying, the inventors observed that the hydroxyl peak of the CDs@PVA film recovered to 3300 cm -1 This indicates that after drying, the carbon dots and PVA are reassembled through hydrogen bonds. It can be seen that water wetting causes structural changes in the CDs@PVA film, while drying restores the original hydrogen bond network of the CDs@PVA film, thereby achieving water stimulus responsiveness.

[0046] Based on the color change of CDs@PVA film in response to ultraviolet light and the reversible color change process stimulated by water, the inventors demonstrated a repeatable optical information writing / erasing experiment. Fig. 9 As shown, the original CDs@PVA film was made into a circular film and placed on filter paper, covered with an opaque cardboard. The optical information was written by ultraviolet light combined with masking irradiation. Under a 120W lamp, the area of ​​the film exposed to UV light showed a "triangle" pattern, while the unexposed area remained green, indicating that the optical information was successfully written. After further removing the cardboard, the film turned completely orange under UV light, and the "triangle" pattern was hidden, realizing the writing and hiding of information. It is worth noting that the pattern can be erased by a simple soaking treatment. After 1mL of water was dropped onto the film, the orange pattern gradually disappeared under UV light, confirming the realization of repeatable optical information writing and erasing. After the film was dried and cooled for 10 minutes, the next round of writing and erasing could be carried out. The entire input-erasure cycle process takes about 15 minutes.

[0047] Example 2

[0048] A method for preparing a CDs@PVA film comprises the following steps:

[0049] S1. Preparation of carbon dots

[0050] S11, 30 mg of naphthalenetetracarboxylic acid and 1.9 g of biuret were mixed and ground evenly, and then the mixture was transferred to a 25 mL beaker, 1 mL of DETN (diethylamine) and 4 mL of deionized water were added, and mixed to obtain a mixed solution;

[0051] S12, placing the mixed solution in a microwave oven, heating it at the defrosting setting for 15 minutes, cooling it naturally to room temperature, then washing the solid with water several times, and finally drying the solid in an oven at 60° C. overnight to obtain white solid carbon dots;

[0052] S2. Preparation of PVA solution

[0053] 10 g of polyvinyl alcohol (PVA) was dissolved in 100 mL of deionized water to obtain a solution, which was placed in an oil bath and heated at 90° C. and 700 r / min for 10 h to obtain a PVA solution with a mass fraction of 10%;

[0054] S3. Preparation of CDs@PVA film

[0055] Take 1 mL of the PVA solution obtained in step S2, mix it evenly with 30 mg of the carbon dots obtained in step S1 and 1 mL of diethylamine solution to obtain a mixture, add the mixture dropwise onto a glass slide, let it stand and dry naturally for 2 h, and then further dry it in an oven at 60 °C to obtain a CDs@PVA film.

[0056] Similar to Example 1, the carbon dots prepared in Example 2 exhibited highly similar performance to that of Example 1, and the prepared CDs@PVA film also had the characteristics of color change in response to ultraviolet light and reversible color change in response to water stimulation.

[0057] Example 3

[0058] A method for preparing a CDs@PVA-1 film comprises the following steps:

[0059] S1. Preparation of carbon dots

[0060] S11, 30 mg of 1,4,5,8-naphthalenetetracarboxylic anhydride and 2.06 g of biuret were mixed and ground evenly, and then the mixture was transferred to a 25 mL beaker, 1 mL of DETN (diethylamine) and 4 mL of deionized water were added, and mixed to obtain a mixed solution;

[0061] S12, placing the mixed solution in a microwave oven, heating it at the defrosting setting for 15 minutes, cooling it naturally to room temperature, then washing the solid with water several times, and finally drying the solid in an oven at 60° C. overnight to obtain white solid carbon dots;

[0062] S2. Preparation of PVA solution

[0063] 10 g of polyvinyl alcohol (PVA) was dissolved in 100 mL of deionized water to obtain a solution, which was placed in an oil bath and heated at 90° C. and 700 r / min for 10 h to obtain a PVA solution with a mass fraction of 10%;

[0064] S3. Preparation of CDs@PVA-1 film

[0065] Take 1 mL of the PVA solution obtained in step S2, mix it evenly with 30 mg of the carbon dots obtained in step S1 and 1 mL of diethylamine solution to obtain a mixture, add the mixture dropwise onto a glass slide, let it stand and dry naturally for 2 h, and then further dry it in an oven at 60 °C to obtain a CDs@PVA-1 film.

[0066] Similar to Example 1, the carbon dots prepared in Example 3 exhibited highly similar performance to that of Example 1, and the prepared CDs@PVA-1 film also had the characteristics of ultraviolet light responsive color change and reversible color change induced by water stimulation.

[0067] Example 4

[0068] A method for preparing a CDs@PEG film comprises the following steps:

[0069] S1. Preparation of carbon dots

[0070] S11, 30 mg of naphthalenetetracarboxylic acid and 2.06 g of biuret were mixed and ground evenly, and then the mixture was transferred to a 25 mL beaker, 1 mL of DETN (diethylamine) and 4 mL of deionized water were added, and mixed to obtain a mixed solution;

[0071] S12, placing the mixed solution in a microwave oven, heating it at the defrosting setting for 15 minutes, cooling it naturally to room temperature, then washing the solid with water several times, and finally drying the solid in an oven at 60° C. overnight to obtain white solid carbon dots;

[0072] S2. Preparation of PEG solution

[0073] Dissolve 10 g of polyethylene glycol (PEG) in 100 mL of deionized water to obtain a solution, put the solution into an oil bath, and heat it at 90° C. and 700 r / min for 10 h to obtain a PEG solution with a mass fraction of 10%;

[0074] S3. Preparation of CDs@PEG film

[0075] Take 1 mL of the PEG solution obtained in step S2, mix it evenly with 30 mg of the carbon dots obtained in step S1 and 1 mL of diethylamine solution to obtain a mixture, add the mixture dropwise onto a glass slide, let it stand and dry naturally for 2 h, and then further dry it in an oven at 60 °C to obtain a CDs@PEG film.

[0076] Similar to Example 1, the carbon dots prepared in Example 4 exhibited highly similar performance to that of Example 1, and the prepared CDs@PEG film also had the characteristics of ultraviolet light responsive color change and reversible color change induced by water stimulation.

[0077] Comparative Example 1

[0078] Comparative Example 1 is the same as Example 1, except that in step S3, diethylamine is not added.

[0079] Test results: Only a small amount of carbon dots in the mixed solution dissolved in water, and the mixed solution showed no ultraviolet light response characteristics under ultraviolet light irradiation. It can be seen that when diethylamine is not added, the carbon dot material does not show light response characteristics.

[0080] Comparative Example 2

[0081] Comparative Example 2 is the same as Example 1, except that in step S3, the amount of diethylamine added is 3 mL.

[0082] Test results: The carbon dot material quickly dissolved in the diethylamine solution, the mixed solution became viscous, and the mixed solution no longer showed the state before irradiation after being irradiated by ultraviolet light, and the light response color change performance was poor. It can be seen that when excessive diethylamine is added, the light response characteristics of the carbon dot material deteriorate.

[0083] Comparative Example 3

[0084] Comparative Example 3 is the same as Example 1, except that in step S3, PVA is replaced by polyvinyl acetal, polyurethane alcohol, and polyglycerol alcohol ester, respectively.

[0085] Test results: The mixed solution cannot be mixed evenly with polyvinyl acetal, polyurethane alcohol, and polyglycerol alcohol ester solutions respectively. The mixed material is gel-like and uneven, and no longer has the color change in response to ultraviolet light and the reversible color change under water stimulation. It can be seen that when PVA is replaced with other inappropriate substances, the mixed material no longer has the reversible color change characteristics under water stimulation.

[0086] Comparative Example 4

[0087] Comparative Example 4 is the same as Example 1, except that in step S1, the amount of naphthalenetetracarboxylic acid added is 200 mg.

[0088] Test results: Naphthalenetetracarboxylic acid was not completely reacted during the reaction, the resulting product was complex and it was difficult to effectively distinguish the intermediate product from the final product. After the mixed product was added to the diethylamine solution, it did not show obvious ultraviolet light response color change. When the mixed solution was added to the PVA solution, it did not show reversible water-stimulated color change characteristics. It can be seen that when an excess of naphthalenetetracarboxylic acid was added, the mixed material no longer had the ultraviolet light response color change and the reversible color change characteristics of water stimulation.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon nanomaterial having photochromic and water-stimulation response, characterized in that: The steps include: A. Preparation of carbon dots containing electron-deficient aromatic imine groups; B. The carbon dots prepared in step A, component A and diethylamine are uniformly mixed in a solvent in a certain proportion and dried to obtain the obtained product; wherein component A is selected from one or more of polyvinyl alcohol, polypropylene alcohol and polyethylene glycol, and the carbon dots are coated in component A; the carbon nanomaterial has photochromic and water stimulus response characteristics.

2. The preparation method according to claim 1, characterized in that In step A, raw material A, biuret and diethylamine are used as precursors to prepare carbon dots by microwave-assisted synthesis; wherein raw material A is selected from one or more of naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic anhydride and phthalic acid.

3. The preparation method according to claim 2, characterized in that: In step A, naphthalenetetracarboxylic acid and biuret are mixed and ground evenly, and then diethylamine and deionized water are added to prepare carbon dots by microwave-assisted synthesis.

4. The preparation method according to claim 3, characterized in that: The mass ratio of naphthalenetetracarboxylic acid to biuret is 2-4:150-250.

5. The preparation method according to claim 4, characterized in that: A mixture of naphthalenetetracarboxylic acid, biuret, diethylamine and deionized water is heated by microwave, cooled naturally to room temperature, washed with water several times, and dried to obtain carbon dots.

6. The preparation method according to claim 4 or 5, characterized in that: The mass volume ratio of naphthalenetetracarboxylic acid and diethylamine is 20-40: 0.5-1.5, unit is g / L.

7. The preparation method according to claim 6, characterized in that: In step B, the mass ratio of carbon dots to component A is 200-400:

1.

8. The preparation method according to claim 7, characterized in that: In step B, the mass volume ratio of carbon dots to diethylamine is 20-40:1, expressed in g / L.

9. A carbon nanomaterial having photochromic and water-stimulation response, characterized in that: The carbon nanomaterial is prepared by the preparation method described in any one of claims 1-8.

10. An application of the carbon nanomaterial according to claim 9 in the field of information encryption and anti-counterfeiting, characterized in that: By utilizing the photochromic and water-stimulation response properties of carbon nanomaterials, information can be repeatedly written, hidden, and erased, and the information can only be read under the stimulation of a specific wavelength of light.